Internalizing objectification: Objectified individuals see themselves as less warm, competent, moral, and human. (15th February 2017) - Loughnan, Steve; Baldissarri, Cristina; Spaccatini, Federica; Elder, Laura
Abstract : People objectify others by viewing them as less warm, competent, moral, and human (Heflick & Goldenberg, 2009, J. Exp. Soc. Psychol ., 45, 598; Vaes, Paladino, & Puvia, 2011, Eur. J. Soc. Psychol ., 41, 774). In two studies, we examined whether the objectified share this view of themselves, internalizing their objectification. In Study 1 ( N = 114), we examined sexual objectification, and in Study 2 ( N = 62), we examined workplace objectification. Consistent across both studies, we found that objectification resulted in participants seeing themselves as less warm, competent, moral (Study 2 only), and lacking in human nature and human uniqueness. These effects were robust to perceiver gender and familiarity (Study 1), and whether another person or a situation caused the objectification (Study 2). In short, the objectified see themselves the manner they are seen by their objectifiers: as lacking warmth, competence, morality, and humanity.